O usuário jovem no centro de atenção psicossocial - Rocha, Patrícia Lorena Resende (2021)
The Center for Psychosocial Care (CAPS) emerged in an ideological, political, and social context that sought greater popular participation in public health and mental health policies. Moreover, the CAPS were created as an alternative to the old mental health treatment modalities, based on isolation and confinement. Although they have since been fulfilling their role of offering a more humanized care and that advocates, above all, the freedom of the subject and reintegration into society, it is necessary to think about the public that is no longer a remnant of the insane asylums, but is experiencing the mental illness in a new era, with different cultural and social contexts. This research sought to study specifically the young users of a CAPS located in a city in the Midwest region of Brazil, with the objective of understanding their perception about the treatment offered by the CAPS. This is a qualitative research, in which a semi-structured interview script was used as an instrument. Eight users, between 18 and 30 years old, participated in the research, six of them female and two male. The interviews were conducted both in CAPS and in the young people's homes, according to their preference, and a thematic analysis of their content was carried out based on the concept of indicators. The results, from the construction of the therapeutic itineraries, pointed out that the search for services at CAPS occurs at the initiative of the family, almost always after initial treatments only with doctors in the private network, with the financial question being a motivation to seek the service in some cases. They also show that there is low adherence of young people to the service, with the majority of them attending CAPS sporadically for medical appointments, which gives the service an outpatient feel. In addition, they point to vulnerabilities that these young people are subject to such as self-injury, suicide attempts, and a restricted support network. Despite this, they mention dreams and plans for the future, as well as support from the closest family nucleus.